ACOUSTIC FACIES AROUND THE INTRUSIVE COMPLEX OF SALAHNAMA AND PANDANG ISLANDS, MALACCA STRAIT - , S.Si., MT., Subarsyah; Albab, Ali; Zulivandama, Shaska Ramdhan; Saputro, Eko; Ali, Arif; Setiadi, Imam; Zulfikar, Muhammad; Nauval, Faris; Rahardiawan, Riza (BULLETIN OF THE MARINE GEOLOGY, 2025)
Salahnama and Pandang Islands lie on the main range of the granite province; both islands are located in the Sunda Shelf, Malacca Straits. These islands are composed of intrusive rocks from Berhala. The rock’s existence will offer a significant contribution to the distribution of surface sediments in the surroundings. The sea dynamics and the geometry of the Malacca Strait will also have an impact on the seabed. Apart from that, global factors such as sea level changes will lead to transformation of the depositional environment and subsurface geology in the strait. Geological conditions of the seabed surface and subsurface can be understood and interpreted based on the acoustic characteristics and reflector patterns of a seismic section. Then, based on the acoustic character and reflector pattern, an acoustic facies can be defined. Seismic data measurements have been carried out around Salahnama and Pandang Islands in 2024. Based on the results of the seismic section, the acoustic facies in the study area are classified into 6 (six), which include AF I – AF VI. Seabed morphological features in the form of sand dunes were identified in the first acoustic facies (AF I); this feature is formed due to geometric aspects, surface currents, and bottom current's which may or may not be triggered by tidal vortices. Acoustic Facies II (AF II) is characterized by sandwave or ripple marks formed by strong seabed currents. AF III was formed after the Last Glacial Maximum (LGM) ended and the depositional environment returned to a shallow marine environment, characterized by a transparent pattern in the seismic section. The erosional truncation at the upper boundary of AF IV indicates a change in the depositional environment from shallow marine to coastal or terrestrial environments during the Last Glacial Maximum period. AF V is acoustic bedrock, and AF VI is characterized by a chaotic pattern, which is interpreted as granitic intrusive rocks.